KONSEP PENDIDIKAN DALAM PERSPEKTIF AL QURAN (KONSEP PENDIDIKAN PEMIKIRAN IBNU SINA) - Nilna Mayang Kencana Sirait (Jurnal At-Tabayyun, 2020)
In the study of Islamic educational philosophy, education is an effort to develop the potential of the services and spiritual learners cognitively, affectively and psychomotorly to make and form human beings who are knowledgeable and technological and make people who believe and fear. Studying the meaning and nature of education in the study of Islamic educational philosophy is actually very relevant to the study of the interpretation of the Qur'an itself. Because the terminology contained in the philosophical study of the essence of education, the purpose of education, educators, learners, methods and curriculum and the process of education all depart from the word of Allah contained in the Qur'an. Ibn Sina's thoughts on education in a structured and comprehensivemanner that discuss the purpose of education, curriculum, learning methods and teachers or educators are the main factors of determinants in education, all of which are in line with the concept of education.